Persekongkolan Dalam Tender yang Mengakibatkan Persaingan Usaha Tidak Sehat - Ginting, Jamin (Pelita Harapan University, 2002)
Since the Unfair Competition Law No. 5year 1999 enacted on 5 March 1999 and effective in mid-year 2000, many actions have been done as the effect of its implementation. One of its efforts is the existence of Business Competition Supervision Commission (KPPU) whose duty makes a report on unfair practice. PT. Caltex Pacific Indonesia (PT. CPI) has been reported as a company that violates article 22 of Unfair Competition Law. This article elaborates basic norms of Law and considerations from KPPU in determining PT. CPI violating article 22 of Unfair Competition Law and sanctions which should be done (based on the Business Competition Supervision Commission decision No. 01/KPPU - L/2001).Â